Clinical features and predictors of atrial fibrillation in patients with light‐chain or transthyretin cardiac amyloidosis - Maria Papathanasiou; Aiste‐Monika Jakstaite; Sara Oubari; Johannes Siebermair; Reza Wakili; Julia Hoffmann; Alexander Carpinteiro; Tim Hagenacker; Andreas Thimm; Christoph Rischpler; Lukas Kessler; Tienush Rassaf; et al. (ESC Heart Failure)
Abstract Aims The study aimed to investigate the prevalence, phenotypic characteristics, and predictors of atrial fibrillation (AF) in patients presenting with cardiac amyloidosis (CA) of light‐chain (AL) or transthyretin (ATTR) type. Methods and results Clinical, biochemical, and echocardiographic data of patients presenting with CA between 2005 and 2020 were retrospectively collected. CA staging was based on established biomarker systems. Binomial logistic regression was run to analyse the effects of clinical variables on the likelihood of AF. The study included 133 patients [53% AL, 41% wild‐type (wt) ATTR‐CA, & 6% hereditary ATTR‐CA]. Mean age was 71 years, and 80% were male patients. AF was diagnosed in 64 (48%) patients (28% in AL‐CA, 80% in wtATTR, 13% in hATTR, P < 0.001). Patients with AF were older (74 vs. 69 years, P < 0.001), more likely to have wtATTR‐CA (67 vs. 16%, P < 0.001), exhibited more often New York Heart Association ≥ III symptoms (66 vs. 45%, P = 0.02) and carried a higher burden of comorbidities. AF patients had lower left ventricular ejection fraction (47 vs. 53%, P < 0.005), higher left atrial volume index (54 vs. 46 mL/m2, P = 0.007), higher pulmonary artery pressure (42 vs. 31 mmHg, P = 0.008), and worse tricuspid annular plane systolic excursion values (17 vs. 20 mm, P = 0.01). Mitral regurgitation ≥ Grade 2 was more frequent in AF (56 vs. 25%, P < 0.001). Higher ATTR‐CA stage was associated with higher AF prevalence (47% vs. 74% vs. 94%, P < 0.001, for Stages I, II, & III, respectively). Higher AL‐CA stage was associated with lower AF prevalence (0% vs. 40% vs. 31% vs. 18%, P < 0.001, for Stages I, II, IIIa, & IIIb, respectively). Three independent predictors for AF were identified in a multivariate logistic regression model with 81.5% classification accuracy: AL type [odds ratio (OR) 0.1, confidence interval (CI) 0.01–0.29, P = 0.001], estimated glomerular filtration rate (OR 0.9, CI 0.93–0.99, P = 0.03), and body mass index (OR 1.3, CI 1.07–1.66, P = 0.01). ATTR amyloidosis was associated with a 10‐fold higher risk of AF. During 1 year follow‐up, only one episode of ischaemic stroke was reported. Conclusions Atrial fibrillation affects nearly half of all patients with CA. Patients presenting with AF have more severe symptoms and higher burden of comorbidities. ATTR type of amyloidosis is the strongest predictor of AF. Prospective screening for occult AF may be considered in ATTR‐CA.